Revitalisasi Pendidikan Islam dalam Upaya Mengantisipasi Perkembangan Iptek Era Revolusi Industri 4.0. - Vita Fitriatul Ulya; Mustofa Tohari (Institut Agama Islam Al-Hikmah Tuban, 2022)
Abstract. This study examines the importance of the role of Islamic education in dealing with the development of science and technology in the era of the industrial revolution 4.0. Through innovations, digitalization has brought major changes in the order of human life. Meanwhile, the achievements of today's Muslim generation are still far from the heyday of Islam in the past. This is of course a special concern for practitioners of Islamic education in realizing an education system that is able to answer global challenges. This research is included in the type of literature review research, where researchers examine in depth and explore data related to the revitalization of Islamic education, both through primary and secondary sources. The data collection method used in this study is to collect literature related to the topic of discussion, namely the revitalization of Islamic education. After all the data has been collected, an in-depth study is carried out and the appropriate sources are sorted. The results of the study indicate that Islamic education has experienced a long history of travel from the heyday of Islam, the period of decline to the challenges of facing the modern era as it is today. With the development of science and technology, humans must be able to adapt to existing progress, and be able to face all future problems and challenges. Therefore, it is necessary to revitalize Islamic education, among others, in fostering the spirit of learning, revitalizing curriculum design, funding sources, and Islamic education infrastructure.